Organisation’s Business Planning and Strategic Decisions - Georgiev, Miroslav (Vilnius University Open Series, 2021)
The report examines the nature and importance of the main objectives trends and strategic goals of the organisation G’s Group over the next few years and the value of proposals for our main and most important products, in particular, the focus will be on the following three main areas: great place to work-teams and culture; sustainable products sustainability and environmental social and financial integrity; strategic clients-supply chain and innovation in products in a lean and resistant way. As a triple bottom line strategy, these objectives are based on achieving a series of economic, environmental and social measurements, a concept that our most valued clients, consumers, employees and members of the local community demand of us.